Tourist Facilities, Tourist Satisfaction, and Interest in Revisiting Tourists in Lake Toba Tourist Attraction - Saragih, Megasari Gusandra (International Journal of Contemporary Sciences (IJCS), 2024)
The research aimed to evaluate the impact of tourist facilities on tourists' revisitation interest, with satisfaction serving as a mediating factor in Lake Toba's tourist destinations. The study involved a sample of 120 visitors to Lake Toba. This investigation utilized a quantitative approach, relying on primary data collected through questionnaires distributed to respondents, using a Likert scale ranging from 1 to 5. The analysis was conducted using a hierarchical structure modeled through Structural Equation Modeling (SEM) with the AMOS-20 (Analysis of Moment Structure) software. The findings reveal that tourist facilities exert a positive and significant influence on both tourist satisfaction and their intention to revisit Lake Toba. Additionally, satisfaction significantly impacts tourists' revisitation interest. As a mediating factor, satisfaction partially mediates the relationship between tourist facilities and tourists' intention to revisit Lake Toba.